Arab Republic of Egypt : Integrated Water Resources Management Plan - World Bank (Washington, DC, 2012)
The challenges facing the water sector in Egypt are enormous and require the mobilization of all resources and the management of these resources in an integrated manner. Changes in the way water resources are currently allocated and managed are inevitable. Accordingly, a National Water Resources Plan for Egypt (NWRP) was launched. The NWRP is a comprehensive document which describes how Egypt will safeguard its water resources in the future, both with respect to quantity and quality, and how it will use these resources in the best way from a socio-economic and environmental point of view. The NWRP needs to be augmented by a transitional strategy including further reform interventions which ensure smooth and enhanced streamlining with Integrated Water Resources Management principles and approaches. The current integrated water resources management plan (IWRM Plan) has been prepared to serve the later concerns and is intended to be a complementary, action-oriented, implementation framework to the NWRP. It addresses the gaps in NWRP and provides for additional measures and provisions which facilitate the transition towards an integrated management approach within the water sector. The IWRM Plan assesses the current water resources management setup and practices along with the ongoing reform efforts led by the MWRI. The Plan identifies the actions agreed upon as major interventions to pursue an effective integrated framework for water management over the next 15 years. Thirty Nine actions falling under 11 major categories are proposed: Institutional reform and strengthening; policies and legislations; physical interventions; capacity building; technological and information systems; water quality; economic and financial framework; research; raising awareness for IWRM; monitoring and evaluation; and trans-boundary cooperation.